Australian Association for Exercise and Sport Science
Website of the Australian Association for Exercise and Sport Science (AAESS) which was formed in 1992 to provide the vehicle and potential to identify, develop, and secure prospective career paths in Exercise Science including Health and Fitness, Sport Science and Exercise Rehabilitation.